The Role of Parents in Supporting Children's Swimming Achievements - Qohhar, Wildan; Pazriansyah, Deni; Ariani, Egiesta Dwi (Department of Physical Education, Faculty of Health Sciences, Universitas Jenderal Soedirman, 2024)
This research analyzes parents' role in supporting children's swimming achievements at the Tirta Winaya Swimming Club, Serang City. This research uses a survey method with a qualitative descriptive approach. The sample in this research is 25 parents of Tirta Winaya swimming athletes in Serang City, and the sampling technique used is total sampling. The instrument used is a questionnaire. These results show that parents have a significant role in attention factors, Facilities and Infrastructure, and environment. However, there needs more attention to nutrition factors. It can be concluded that the role of parents in supporting children's swimming achievements at the Tirta Winaya Swimming Club, Serang City, is maximal.